Thomas Jefferson papers - Jefferson, Thomas, 1743-1826.
Microfilm of correspondence from the Jefferson papers and other collections in the New-York Historical Society. Correspondents include Albert Gallatin, Horatio Gates, Rufus King, and Baron von Steuben.
Microfilm of originals in the New-York Historical Society (New York).
New-York Historical Society
U.S. president, vice president, and secretary of state; diplomat, architect, inventor, planter, and philosopher.
Keywords: Gallatin, Albert, -- 1761-1849 -- Correspondence; Gates, Horatio, -- 1728-1806 -- Correspondence; King, Rufus, -- 1755-1827 -- Correspondence; Steuben, Friedrich Wilhelm Ludolf Gerhard Augustin, -- Baron von, -- 1730-1794 -- Correspondence; Presidents -- United States